2019
DOI: 10.3390/cells8121500
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ Family Signaling Pathways in Pluripotent and Teratocarcinoma Stem Cells’ Fate Decisions: Balancing Between Self-Renewal, Differentiation, and Cancer

Abstract: The transforming growth factor-β (TGFβ) family factors induce pleiotropic effects and are involved in the regulation of most normal and pathological cellular processes. The activity of different branches of the TGFβ family signaling pathways and their interplay with other signaling pathways govern the fine regulation of the self-renewal, differentiation onset and specialization of pluripotent stem cells in various cell derivatives. TGFβ family signaling pathways play a pivotal role in balancing basic cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 302 publications
(388 reference statements)
0
27
0
Order By: Relevance
“…Also the formula in our previous study was shown to promote ovarian follicle developing in 4-vinylcyclonhexene diepoxide (VCD)-induced POI rats, and the gene expression of transforming growth factor beta-activated kinase 1 (TAK1) was significantly different between the the control, VCD and VCD + HYYKF groups [ 18 ]. TAK1 is an important signaling molecule in the transforming growth factor beta (TGF-β) signaling pathway, and the TGF-β signaling pathway has a wide range of regulating functions by interacting with other pathways and plays a critical role in the physiological and pathological processes of pluripotent stem cells [ 19 ]. We hypothesized that HYYKF could enhance the treatment effect of ESCs on POI by regulating the TGF-β/TAK1 pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Also the formula in our previous study was shown to promote ovarian follicle developing in 4-vinylcyclonhexene diepoxide (VCD)-induced POI rats, and the gene expression of transforming growth factor beta-activated kinase 1 (TAK1) was significantly different between the the control, VCD and VCD + HYYKF groups [ 18 ]. TAK1 is an important signaling molecule in the transforming growth factor beta (TGF-β) signaling pathway, and the TGF-β signaling pathway has a wide range of regulating functions by interacting with other pathways and plays a critical role in the physiological and pathological processes of pluripotent stem cells [ 19 ]. We hypothesized that HYYKF could enhance the treatment effect of ESCs on POI by regulating the TGF-β/TAK1 pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the zygote and early two-cells, from the comparisons between the mid-late two-cells and TBLCs, TBLCs showed high expression levels of pluripotency genes and low expression of totipotency genes. In the predicted pathway regulation analyses, many of the differentiation-related genes are enriched in the TBLCs, including Tgf1 and Fgf2 [16,19].…”
Section: Discussionmentioning
confidence: 99%
“…When identifying potential target genes of the significantly up-and down-regulated miRNAs, we found regulatory molecules in Wnt signaling pathway, which play an important role in regulation of inflammation, oxidative stress and senescence 64 . Interestingly, our distinct secreted miRNAs were predicted to regulate a dynamic crosstalk of Wnt and another prominent pathway, NOTCH via targeting SMADs, which are also well-know nmediators of inflammatory, fibrotic, oxidative, proliferative, metabolic and angiogenic events [65][66][67] . The NOTCH super-signaling pathway plays an emerging role controlling key steps in the immune system and tissue homeostasis during repair and regeneration 68 .…”
Section: Reactomepathway Enrichment Analysis #Genes P-valuementioning
confidence: 99%